Images in Logical-and-Linguistic Artificial Intelligence Systems - Kobrinskii, Boris A. (British Journal of Healthcare and Medical Research, 2019)
Visual images are holistic, and when verbalized there is a partial loss of semantic content. However, it should be noted the lack of effectiveness of decision support systems only when using images without an effective context, and systems that do not include holistic images. Inclusion of images in the knowledge base of intelligent systems can significantly improve their effectiveness. At the stage of formation of intermediate diagnostic hypotheses, the system will present to the user (physician) a hypothesis specific to the verbal and visual characteristics. At the same time, it is necessary to take into account the need to use fuzzy logic at the stages of the derivation of solutions. The subsequent process will depend on the physician’s confidence in the coincidence of the image of the diagnosed patient with the image(s) in the knowledge base of the intellectual system.